High-performance CH3NH3PbI3 perovskite solar cells fabricated under ambient conditions with high relative humidity. (17th September 2015) - Lei, Binglong; Eze, Vincent Obiozo; Mori, Tatsuo
Abstract: Hygroscopic perovskite solar cells are commonly fabricated under conditions of inert atmosphere or low relative humidity (RH). To generate high-performance perovskite light-absorbing layers for super power conversion efficiency (PCE), we fabricated CH3 NH3 PbI3 solar cells under ambient conditions (RH = 42–48%) by a flowing gas directly from high-RH air. The primary advantage of this technique, together with the casting of a hot solution and quick conduction, enabled us to achieve the highest and average PCEs of 16.32 and 14.27% respectively, with an extremely small deviation of 0.49%. Our research will be of significance for fabricating highly efficient and reproducible perovskite photovoltaics.